The Impact of the Dark Side of Leadership on the Psychological State of Employees after the Covid-19 Pandemic: : A Psychological Perspective - Hillman Wirawan (Har Press Indonesia, 2023)
This study aims to review the adverse effects of the dark side of leadership on employees’ psychological states, including distress and anxiety, after the COVID-19 pandemic, through the lens of psychological theories. A literature review was used to examine the dark side of leadership, which included any form of abusive, toxic, or destructive behaviors and characteristics that negatively affect the psychological states of employees. The effect on employees’ psychological state is crucial as it can influence their attitudes and performance. The Conservation of Resources and the Psychological Contract theory were employed to explain the emergence of the dark leaders’ behaviors and their consequences on employees’ psychological states in anticipation of extreme organizational changes after the pandemic. The employees’ psychological resources could be depleted due to exposure to abusive leaders while adapting to organizational changes post the pandemic. Also, the mistreatments from the destructive leaders could breach the employees’ psychological contract. The emergence of dark leadership practices might cause psychological distress. Previous psychological studies suggest that the psychological resources of employees can be replenished by seeking social support, while the organization can contribute by implementing intervention programs.